Decision making and decision taking: GSS and complex adaptive systems theory - Whiteley, Alma; Wood, E. (Curtin University of Technology, 2000)
The paper reports on research to explore the anticipatory capabilities of individuals when faced with a decision scenario and when asked to take into account the anticipated responses of the recipient of the decision ? the decision taker. It reports on the effectiveness of Group Support Systems (GSS) technology in emerging imaginative and anticipatory data. The assumption is that the decision maker can involve the decision taker as an adaptive agent in the decision maker?s final (collapsed) decision choice. GSS proved to be easy for individuals to use and productive in output. The calibre of the imaginative and anticipatory stories suggested that the mechanistic appearance of computer-aided data collection did not have an adverse effect.Theoretically, there is a preponderance in decision theory of rational choice making but little to see in decision research about the drama of human interaction. Typically, literature focuses on decision formulation and often the decision taker role is somewhat taken for granted as being either compliant or non compliant. The idea in this research, stimulated by chaos and complex adaptive systems theory, is to bring the decision taker inside of the decision maker?s self organising and sense making processes. In particular, the suggested human capabilities of anticipation, imagination and personal schema building of ?if then? rules are being explored.Systems theory is an important element of the theoretical framework, particularly as Group Support Systems technology was used as the main data collection device. Given the nature of the research issue, an argument is presented suggesting that GSS and indeed much research in the systems area continues to be affected by antecedents of positivist science. Studying adaptivity in decision making/taking is largely a constructivist undertaking. However, there is also a sense of the real and rational. Complexity theory may provide a way to incorporate both perspectives in a similar way to physicists now talking about a qualitative science.